PENGARUH RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN ROKOK DI BURSA EFEK INDONESIA - Soesilawati Soema Atmadja (LP2M Universitas Bina Bangsa, 2023)
This study aims to empirically examine the effect of partial and simultaneous financial ratios (Current Ratio, Net Profit Margin, Debt to Asset Ratio, Total Assets Turn Over) on Profit Growth in Cigarette Companies listed on the Indonesia Stock Exchange for the 2014-2021 period. The population in this study was cigarette companies listed on the Indonesia Stock Exchange and the sampling technique used purposive sampling techniques, with a final sample number of 4 companies. The analysis technique in this study uses multiple linear regression analysis with IBM SPSS Statistical 26 software. From the results of the study, it is partially shown that the Current Ratio variable has no effect on Profit Growth, For the Net Profit Margin variable, Debt to Asset Ratio variable, Total Assets Turn Over variable, it partially have a significant effect on Profit Growth. Simultaneously shows the variables have a significant effect on Profit Growth. For the results of the calculation of the Coefficient of Determination shows a value of 0.765 or 77%.